Ethical challenge of student-participants using a research survey for giving course feedback - Helena Siipi; Susanne Uusitalo (Springer, 2024)
Abstract Conducting research with one's students as participants can have various challenges. We describe one particular challenge we have encountered when conducting research surveys with participants who had been students of a doctoral course taught by us. Some participants gave course feedback in the research. This may indicate blurring of the roles of student and research participant. Blurring is problematic from the perspectives of research ethics and research integrity. Problems may arise concerning voluntariness, confidentiality and the quality of data. We suggest possible ways of preventing this blurring. These concern (1) the timing of the research in relation to the course, (2) information for the participants, (3) the recruitment practice and (4) the format of the survey questions.